Chronic toxicity of crude ricinine in rats assessed by 1H NMR metabolomics analysis1. Issue 34 (15th April 2015) - Guo, Pingping; Wei, Dandan; Wang, Junsong; Dong, Ge; Zhang, Qian; Yang, Minghua; Kong, Lingyi
<x xml:space="preserve">Abstract</x> A 1H-NMR based metabolomics approach combined with OSC-PLS-DA was applied to investigate the chronic toxicity of crude ricinine from castor bean shell in rats for the first time.